Strategi Pemberdayaan UMKM Berbasis PKK Di Desa Wisata Sekapuk Kabupaten Gresik - Ermawati, Yuli; Pujianto, Pujianto (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2021)
The role of tourist destinations on Regional Original Income is very large. Efforts to boost the tourism industry must not forget the development of Micro, Small and Medium Enterprises (MSMEs). Currently, MSME development efforts are translated into government policies through 3 (three) priority programs of the Ministry of Cooperatives and MSMEs. Another policy that is also interesting to discuss is the allocation of village funds. Various real efforts and strategies have been carried out by several parties in developing MSMEs. The purpose of this study is to explore information about financial governance, policies and empowerment systems carried out by the relevant village government, map the constraints of implementing MSME empowerment in the Tourism Village area, then make the right pattern/model for empowering MSMjjjEs in the Tourism Village area in Gresik Regency. The method used in this research is qualitative in the hope of digging deeper into the information needed to answer the objectives of the research. The object of this research is Sekapuk Gresik Village, which is known as the billionaire village. The results showed that the empowerment of MSMEs in Sekapuk Tourism Village came from the independent management of the PKK. The synergy between the PKK and the Village Government is a milestone in the independence of the MSME empowerment policy and management system. The role of the Village Government is to provide facilities and stimulation for the independence of the sustainability of MSMEs under the PKK. The profit-sharing system is an effective way to encourage the growth of MSMEs which is synergized with the management of tourist areasÂ Keywords: MSME Empowerment Model, Tourism VillageÂ Â